2014
DOI: 10.2147/ott.s65238
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes from dose-escalated image-guided intensity-modulated radiotherapy with androgen deprivation: encouraging results for intermediate- and high-risk prostate cancer

Abstract: PurposeDose-escalated (DE) radiotherapy in the setting of localized prostate cancer has been shown to improve biochemical disease-free survival (bDFS) in several studies. In the same group of patients, androgen deprivation therapy (ADT) has been shown to confer a survival benefit when combined with radiotherapy doses of up to 70 Gy; however, there is currently little long-term data on patients who have received high-dose intensity-modulated radiotherapy (IMRT) with ADT. We report the long-term outcomes in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Finally, our experience and results demonstrate that ‘Not all rural and regional centres are low‐volume centres’. The NCCI has previously published IMRT outcomes for other cancer sites, which support our notion that providing IMRT in rural or regional centres can produce comparable outcomes as large tertiary centres …”
Section: Discussionsupporting
confidence: 79%
“…Finally, our experience and results demonstrate that ‘Not all rural and regional centres are low‐volume centres’. The NCCI has previously published IMRT outcomes for other cancer sites, which support our notion that providing IMRT in rural or regional centres can produce comparable outcomes as large tertiary centres …”
Section: Discussionsupporting
confidence: 79%
“…Of interest in our study was that there was no significant benefit seen for SpaceOAR patients in terms of proctitis or faecal incontinence. However, the baseline rates of these toxicities in our patients is very low (as previously reported), and it is possible larger numbers of patients would be required to determine any differences. In addition, we do not report long‐term late toxicity which may better demonstrate any potential benefits of SpaceOAR rectal dose reductions.…”
Section: Discussionmentioning
confidence: 67%
“…This final stage of the class solution demonstrated that 89% of prostate patients met treatment criteria outright (S. Greenham, personal communication). Further research is required to determine whether prostate class solutions can maintain or improve upon the clinical and patient-reported outcomes 5,6,15 of dose-escalated image-guided IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were volumed using magnetic resonance imaging (MRI) and computed tomography (CT) fusion 4 and treated to 81 Gy as previously described. 5,6 Planning criteria and OAR constraints are summarised in Tables 1 and 2 and were based on evidencebased guidelines (EviQ recommendations). 7 Minor violations were acceptable when all reasonable efforts to achieve ideal constraints had been made.…”
Section: Methodsmentioning
confidence: 99%